Penerapan Pidana Korporasi pada Bank dalam Tindak Pidana Perbankan Sesuai PERMA Nomor 13 Tahun 2016 - Dwi Mardianto; Irsyad Noeri; Suyadi Suyadi (Universitas Muhammadiyah Jember, 2020)
Corporate Crime in the banking sector in particular there is not a single law related to banking regulating how to penalize banking corporations, but with the presence of Law Number 21 of 2011 concerning Financial Services Authority and Supreme Court Regulation Number 13 of 2016 concerning Procedures Handling of Criminal Cases by Corporations is a way out of the legal vacuum because even though the Supreme Court Regulation is an internal provision that binds the Judge as the court decision-maker, the decision is binding on the public.